Pengaruh Indeks Pembangunan Manusia dan Tingkat Kemiskinan Terhadap Pertumbuhan Ekonomi di Provinsi Aceh - Salpina, Purjah; Nasir, Muhammad; Farlian, Talbani; Varlitya, Cut Risya (Jurnal Ilmiah Ekonomi Terpadu (Jimetera), 2026)
This paper aims to analyze the effect of the Human Development Index (HDI) and poverty levels on economic growth in Aceh Province during the period 2015–2024. The research employs a quantitative approach using panel data regression that combines time series and cross-sectional data from 23 districts/cities in Aceh. The data used are secondary data obtained from the Central Bureau of Statistics (BPS). The study includes two independent variables, namely the Human Development Index and poverty level, while the dependent variable is economic growth. The results indicate that HDI has a positive and significant effect on economic growth, implying that improvements in education, health, and living standards strengthen productivity and foster regional economic growth. Conversely, poverty has a negative and significant impact on economic growth, as high poverty levels limit consumption, investment, and human capital quality. The study suggests improving human capital through education and health, controlling poverty through economic empowerment, and integrating human capital development policies with poverty alleviation strategies.